Role of Ayurveda in the Management of Manas Roga (Mental Disorders): A Review - Badhoria, Anil; Sharma, Y k (International Research Journal of Ayurveda & Yoga, 2021)
An eternal science of healthy living treasure deals with physical, psychological and spiritual well-being of the human beings which covers all the aspects of human life. It is not materialistic science but a physiological and factual truth, which enhanced by our great sages through experienced logic and power of wisdom. This unique ancient Indian wisdom has survived vividly down the ages is flourishing in the present times in newer dimensions attracting the attentions globally. Depression is a very common mental disorder which affects way of thinking and behavior of person. Ayurveda aims at preservation and promotion of heath, and prevention and cure of diseases through the concepts of positive physical and mental health. Management of mental disorders or psychological medicine was an area of specialization even during Samhita period. Manas chikitsa (treatment of Mental Disorders) Ayurveda recommends preventive medicine. Correct behavior, balanced–diet, and non suppression of natural urges, following daily and seasonal health regimens are integral part of the Manas chikitsa. Ayurveda advocates use of nervine-tonics like Brahami (Bacopa monnieri), Ashwagandha (Withania somnifera), Guduchi (Tinosporia cordifolia), Yastimadhu (Glycyrrhiza glabra) and Vacha (Acromus calamus) for preventing onset of Manas roga. (Mental Disorders)